Magnetic nanoparticles in nanomedicine: a review of recent advances - Wu, Kai; Su, Diqing; Liu, Jinming; Saha, Renata; Wang, Jian-Ping (Nanotechnology, 2019)
Nanomaterials, in addition to their small size, possess unique physicochemical properties that differ from bulk materials, making them ideal for a host of novel applications. Magnetic nanoparticles (MNPs) are one important class of nanomaterials that have been widely studied for their potential applications in nanomedicine. Due to the fact that MNPs can be detected and manipulated by remote magnetic fields, it opens a wide opportunity for them to be used in vivo. Nowadays, MNPs have been used for diverse applications including magnetic biosensing (diagnostics), magnetic imaging, magnetic separation, drug and gene delivery, and hyperthermia therapy, etc. Specifically, we reviewed some emerging techniques in magnetic diagnostics such as magnetoresistive (MR) and micro-Hall (μHall) biosensors, as well as the magnetic particle spectroscopy, magnetic relaxation switching and surface enhanced Raman spectroscopy (SERS)-based bioassays. Recent advances in applying MNPs as contrast agents in magnetic resonance imaging and as tracer materials in magnetic particle imaging are reviewed. In addition, the development of high magnetic moment MNPs with proper surface functionalization has progressed exponentially over the past decade. To this end, different MNP synthesis approaches and surface coating strategies are reviewed and the biocompatibility and toxicity of surface functionalized MNP nanocomposites are also discussed. Herein, we are aiming to provide a comprehensive assessment of the state-of-the-art biological and biomedical applications of MNPs. This review is not only to provide in-depth insights into the different synthesis, biofunctionalization, biosensing, imaging, and therapy methods but also to give an overview of limitations and possibilities of each technology.